Risk and the Corporate Structure of Banks. (IMF Working Papers; Working Paper ;, 2010)
We identify different sources of risk as important determinants of banks' corporate structures when expanding into new markets. Subsidiary-based corporate structures benefit from greater protection against economic risk because of affiliate-level limited liability, but are more exposed to the risk of capital expropriation than are branches. Thus, branch-based structures are preferred to subsidiary-based structures when expropriation risk is high relative to economic risk, and vice versa. Greater cross-country risk correlation and more accurate pricing of risk by investors reduce the differences between the two structures. Furthermore, the corporate structure affects bank risk taking and affiliate size.